Quality improvement interventions to decrease severe neonatal hyperbilirubinemia through virtual facilitation in two hospitals in Ghana - Indira Narayanan; Jayashree Ramasethu; Jeffery Kodjo Arhin; Ashura Bakari; Elliot Akoto (Journal of Global Health Economics and Policy, 2025)
# Background Severe neonatal hyperbilirubinemia (SNH) remains a major health challenge in Ghana, often leading to avoidable exchange transfusions (ET) and long-term consequences for newborn survival and quality of life. # Methods Quality improvement (QI) interventions targeting SNH in inborn neonates ≥34 weeks gestation were implemented and evaluated in two Level II hospitals in Ghana. Due to the COVID-19 pandemic, planned in-person workshops were replaced with virtual collaboration using Zoom, WhatsApp, and Google Drive, coordinated by Georgetown University faculty. # Results Virtual engagement enabled teams to identify delays in care-seeking and implement corrective measures. Key strategies included interactive health education during antenatal care and prior to discharge, daily ward rounds by trained physicians, and the use of context-appropriate outcome indicators. In Hospital A, these interventions led to a 31.3% reduction in SNH cases and a 67.8% drop in ETs within three months, despite challenges such as the early discharge of low-risk mothers and newborns. As a balancing measure, there was an increase in early post-discharge visits for mild jaundice, most of which did not require treatment. Hospital B reported more variable outcomes, likely due to a smaller number of SNH cases. # Conclusions Digital facilitation of QI interventions—supported by targeted counselling, routine postnatal monitoring, and appropriate indicators—proved effective in reducing SNH and unnecessary ETs. Sustained improvements will require broader health system strengthening, including enhanced community outreach, improved transport, access to transcutaneous bilirubinometers, and reliable serum bilirubin testing.